Ocular cytochrome P450s and transporters: roles in disease and endobiotic and xenobiotic disposition. (August 2014) - Nakano, Mariko; Lockhart, Catherine M.; Kelly, Edward J.; Rettie, Allan E.
Abstract Drug metabolism and transport processes in the liver, intestine and kidney that affect the pharmacokinetics and pharmacodynamics of therapeutic agents have been studied extensively. In contrast, comparatively little research has been conducted on these topics as they pertain to the eye. Recently, however, catalytic functions of ocular cytochrome P450 enzymes have gained increasing attention, in large part due to the roles of CYP1B1 and CYP4V2 variants in primary congenital glaucoma and Bietti's corneoretinal crystalline dystrophy, respectively. In this review, we discuss challenges to ophthalmic drug delivery, including Phase I drug metabolism and transport in the eye, and the role of three specific P450s, CYP4B1, CYP1B1 and CYP4V2 in ocular inflammation and genetically determined ocular disease.